2017
DOI: 10.1016/bs.mie.2017.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virus-Like Particle-Based Tumor-Associated Carbohydrate Immunogen in a Mouse Tumor Model

Abstract: Tumor-associated carbohydrate antigens (TACAs) are attractive targets for anticancer vaccine development. Due to the low immunogenicity of TACAs, a powerful carrier system is needed to boost immune responses. Virus-like particles (VLPs) are an exciting platform for delivering TACAs to the immune system. The high symmetry of VLPs enables the display of TACAs in an organized manner, which in turn can potently activate antibody secreting B cells, eliciting high titers of antiglycan IgG antibodies. In this chapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…Scientists have utilized VLPs as a vaccine template to display TACAs. Specifically, the Tn antigen "N-acetylgalactosamine monosaccharide structure" has been chemically coupled to Qβ-VLPs resulting in the display of about 300-400 copies of Tn antigens on the VLPs' surface (Sungsuwan et al, 2017). The results of the study indicated that Qβ-Tn vaccine can elicit significantly higher IgG Ab titers when compared to the control group immunized with Qβ-VLPs only without Tn antigen.…”
Section: Vlp-based Vaccines Against Hepatocellular Carcinomamentioning
confidence: 99%
“…Scientists have utilized VLPs as a vaccine template to display TACAs. Specifically, the Tn antigen "N-acetylgalactosamine monosaccharide structure" has been chemically coupled to Qβ-VLPs resulting in the display of about 300-400 copies of Tn antigens on the VLPs' surface (Sungsuwan et al, 2017). The results of the study indicated that Qβ-Tn vaccine can elicit significantly higher IgG Ab titers when compared to the control group immunized with Qβ-VLPs only without Tn antigen.…”
Section: Vlp-based Vaccines Against Hepatocellular Carcinomamentioning
confidence: 99%
“…The preliminary data shown here on the quality, magnitude and uniqueness of the immune response is very encouraging. First, the antibody response was quite respectable for a simple nanoparticle system and compares well with other TACA-based vaccine antibody titers that were generated from either the fully synthetic platforms of Boons, et al 86,87 , the Q-beta-based platforms of the Huang lab 34 or the MUC4 glycopeptide Tetanus Toxoid conjugates of the Kunz group. 88 The work from Kunz et al, is most relevant to the present work, as this is the only other group that has used MUC4 tandem repeat TACA-containing glycopeptide units in their work.…”
Section: Discussionmentioning
confidence: 52%
“…14,28 Some examples of TACA/nanoparticle-based platforms for cancer immunotherapy include, 1) liposome and lipid-based particles, 29 2) Metallic, and/or ferromagnetic particles [30][31][32] , 3) synthetic biodegradable polymers or hydrogels 33 and 4) Virus-Like Particles (VLPs). 17,34,35 Of the metallic particles, gold nanoparticles (AuNPs) have emerged as the most versatile and hence most utilized for various therapeutic applications. They can be easily synthesized in a size selective manner and be coated with most any appropriately functionalized molecular family (proteins, small molecules, carbohydrates, lipids).…”
Section: Introductionmentioning
confidence: 99%
“…These MS2-L2 VLPs can induce high antibody titers in mice and are cost-effective vaccine candidates against HPV; however, HPV vaccines with greater cross-protection should be further evaluated to prevent more types of HPV (Zhai et al, 2017). Recently, Qβ VLPs have been applied as carriers for the development of carbohydrate-based anticancer vaccines (Sungsuwan, Wu & Huang, 2017). Additionally, researchers have developed a size-exclusion chromatography-based purification method for an VLP-based influenza A vaccine derived from the MS2 phage that displays an epitope from the extracellular domain of the IAV matrix two protein.…”
Section: Virus-like Particles As Built-in Adjuvant Platformsmentioning
confidence: 99%